Activity of two Streptococcus mutans bacteriocins in the presence of saliva, levan, and dextran. - Delisle, A L (1976)
The extracellular dextrans produced from sucrose by Streptococcus mutans strains BHT and GS-5 did not prevent the synthesis or release of active bacteriocins by these two strains. In addition, several streptococci that were genetically sensitive to these bacteriocins, and that could synthesize a variety of extracellular dextrans and levans from sucrose, remained phenotypically sensitive when grown in the presence of sucrose. Bacteriocin activity was not altered by treatment with high-molecular-weight dextran or by human saliva. The bacteriocins produced by, and active against, S. mutans thus appear to be capable of acting in vivo and may play a role in regulating the bacterial ecology of the oral cavity.